DIE DOEL VAN GODSDIENSONDERRIG OP SKOOL - Kotzé, Kobus (Scriptura, 1982)
Aims of religious instruction at school The goal aimed at in the teaching of any subject has a profound effect on the method and approach used in the actual instruction. This article investigates the aims of Biblical Instruction by means of a short survey of a few different approaches to the subject, in order to find a few determinants which could help us to formulate our own aims for Biblical Instructions.